Implementation of digital learning using interactive multimedia in excretory system with virtual laboratory - Heru Setiawan; Wiwi Isnaeni; F. Putut Martin Herry Budijantoro; Aditya Marianti (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2015)
The aim of this study are (1) Developing an interactive multimedia with virtual laboratory in excretory system for senior high school students (2) determine the eligibility of digital multimedia of excretory system (3) determine the effectivity of digital learning using interactive multimedia to improve student’s achievement and student activities of excretory system. This research was conducted in senior high school in Indonesia at SMA 1 Jepon, Blora for 2 month. The research approach using Educational Research and development including: (1)research and information collecting (2)planning (3) develop a preliminary form of product (4) preliminary field testing, validation of media by experts. (5) main product revision, (6)field testing (7)operational product revision (8) operational field testing, (9) the final product revision. The results showed that digital media of excretory system with virtual lab is outstanding criteria (91.17%) based on 2 expert validation result. Then on prelimenary field testing, the students give outstanding criteria (84.38%), and operation field testing is 92.19%. Digital learning using interactive multimedia also improve student activities, students who achieve the active criteria is 90,63%. Based on the results of research and discussion, can be concluded that digital multimedia of excretory system is very eligible, get possitive response from students and teacher, and effective to improve student achievement and student activity as excretory system media in senior high school.